Rancangan Program Aplikasi Al-Faraidh sebagai Media Pembelajaran Mawaris di MAN Model Banda Aceh - Amru Sujud; Juanda BJ; Sandy Vrianda (KITA Institute, 2017)
This study aims to design a new system and method of application program Al-Faraidh as a medium of learning fiqih mawaris in MAN Model Banda Aceh. This research uses qualitative descriptive method, that is by collecting data through interview with fiqih teachers and literature study. The study of jurisprudence is difficult to achieve the expected competence, mawaris calculation is also still done manually. Students tend to be less interested in learning fiqih mawaris because it is considered too difficult. Therefore it is necessary to design an application program as a learning medium that facilitates and attracts students' attention. The design of the web-based application program can process the data muwaris (person who left the heirs), data of heirs along with his position against muwaris, heirs, muwaris reports, and recapitals report on the division of inheritance. The application program is expected to be an effective solution of the problem, thus simplifying the process of calculating the inheritance, especially in the process of learning.